Lady,s Cupcake / Siti Rasyida Jamaluddin... [et al.] - Jamaluddin, Siti Rasyida; Nasir, Dayang Aslina; Zulkifli, Nurul Afiqah; Yusof, Izyan Nafisah (2012)
ENT 300 or Fundamental of Entrepreneurship is compulsory for 5th semester Diploma in Culinary Arts students. In this subject, we are learning about entrepreneur. It is vital for us to know about the entrepreneur world due to our profession after study is commonly related to entrepreneur. Producing food is a big opportunity in entrepreneur world, thus it related to our major. Firstly, this subject teaches us to know about the entrepreneur world like, how to created a business, how to make an agreement and others. In entrepreneur, people that come to this world should the key entrepreneur motivation. Moreover, in this subject, we are also have to create a business and manage to make the business plan start from administration plan, marketing plan, operation plan and lastly financial plan. From the assignment given, we had an opportunity to learn and feel the experience during the task given.